(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Bangladesh has vast char area but most of the char lands are not suitable for crop production. So the present study was undertaken to examine the suitability of crop production by assessing adoption, relative profitability, marketing system, production and marketing problems of rabi season groundnut in char lands of Faridpur, Jamalpur, and Kishoreganj districts during 2013-2014. The sample size of the study was 225 including 90 groundnut farmers and 135 traders. The study revealed that the highest (56%) percent of groundnut farmers cultivated Dhaka-1 variety and only 23% of all farmers cultivated BARI chinabadam-8.The per hectare production cost of groundnut was Tk 61,547, net return was Tk.42,033 and BCR was 1.68. The partial budgeting analysis showed that if the farmers cultivated groundnut instead of its competitive crops, they would receive Tk. 24,445 additional to sesame and Tk.21,990 additional to wheat cultivation. The average estimated marketing costs was highest (Tk.1388/quintal) for Stockist and lowest (Tk.55/quintal) for Arathdar. Net marketing margin was also highest (Tk.1212/quintal) for Stockist and lowest (Tk.59/quintal) for Arathdar. Marketing chain-v was the most efficient than other five chains because it has single involvement of intermediary. The major problems identified by farmers were lack of irrigation facilities (34%), low rate of seed germination (31%), and lack of cultivable land (29%). Major marketing problems were lack of cash capital (82%), and lack of storage facilities (55%) etc. Arrangement of institutional credit with low interest rate (80%), collateral free credit (45%), and arrangement of storage facilities (72%) were the traders opinion to minimize the marketing problems of groundnut. Therefore the study will be helpful to increase groundnut cultivation and improved the marketing system in char lands of Bangladesh. Bangladesh J. Agril. Res. 41(4): 695-711, December 2016